Manufatura e caracterização mecânica de painéis estruturais compósitos para projetos de veículos de competição. - Lopes, Gregory Aguilera (2023)
Due to evolution of development high performance composite, these have been increasingly used in racing car components, because the good trade-of between mass/stiffness incorporated to high levels of driver safety risk. The vehicle's chassis is an important part that can provide up to more than half of the car's total weight. The carbon fiber composite chassis, known as “monocoque”, currently has a more expensive manufacturing process than conventional ones made of stamped steel sheet metal or tubular structure, however, its mechanical properties cannot be replaced by another material keeping the same characteristic of low specific weight. At low budget teams, a feasibility study for the manufacture and maintenance of this component is necessary. The target of this project is to design the optimized sandwich panels, with the enough amount of carbon fiber fabric reinforcement, with the correct combination of the direction in the stacking of the layers, the thickness and kind of core material. The objectives involve maintaining the compromise to the combination of materials according to the minimum mechanical properties to comply with the Formula SAE 2022 rules category, associated with low specific weight and a cheaper process. The vacuum bag lamination process was used, using a glass table as a “mold” for the composite sandwich panels. The mechanical properties of the panels were characterized by 3-point bending test, perimeter shear test, Shore D hardness and the surface morphology and adhesion were analysed by Scanning Electron Microscopy (SEM). Through the results of the tests of this project, it is intended to generate a predictive model of the number of layers as a function of the weight of the fabric, and the thickness of the aramid core, with the mechanical properties necessary to dimension each part of the chassis. After the development of this project, it is intended to apply the composites developed in the manufacture of a Formula SAE monocoque chassis using the moldless method process. Highlighting the laminate with a low-density foam core, where it was possible to get mechanical properties equivalent to the structural requirements of a steel space frame chassis.